b - Wang, Jianyong; Cellary, Wojciech; Wang, Dingding; Wang, Hua.; Chen, Shu-Ching.; Li, Tao.; Zhang, Yanchun; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This two volume set LNCS 9418 and LNCS 9419 constitutes the proceedings of the 16th International Conference on Web Information Systems Engineering, WISE 2015, held in Miami, FL, USA, in November 2015. The 53 full papers, 17 short and 14 special sessions and invited papers, presented in these proceedings were carefully reviewed and selected from 189 submissions. The papers cover the areas of big data techniques and applications, deep/hidden web, integration of web and internet, linked open data, semantic web, social network computing, social web and applications, social web models, analysis and mining, web-based applications, web-based business processes and web services, web data integration and mashups, web data models, web information retrieval, web privacy and security, web-based recommendations, and web search.
Big data techniques and applications -- Deep/hidden web -- Integration of web and internet -- Linked open data -- Semantic web -- Social network computing -- Social web and applications -- Social web models -- Analysis and mining -- Web-based applications -- Web-based business processes and web services -- Web data integration and mashups -- Web data models -- Web information retrieval -- Web privacy and security -- Web-based recommendations -- Web search.
Keywords: Information storage and retrieva; Database management; Computer Communication Networks; Software engineering; Data mining; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Computer Communication Networks; Software Engineering; Data Mining and Knowledge Discovery